Is Sustainability a Pattern of Solution in a Functional State Space? - Williams (My University, 2022)
Human-Centric Functional Modeling has been proposed as a universal approach towards defining representations of the behavior of systems in terms of “functional state spaces”. Such descriptions are hypothesized to be complete in terms of having the capacity to represent all the behavior the system is capable of displaying. This paper provides a brief exploration of Human-Centric Functional Modeling, how it might be used to model the behavior of the cognitive system in terms of a functional state space, and how cognitive complexity might be defined as a property in this functional state space of the cognitive system. Assuming that functional state spaces can be defined for other systems as well, this paper explores the questions that must be asked in considering whether this hypothetical expression for complexity in the functional state space of the cognitive system systems represents a general pattern for defining complexity in any functional state space, and whether complexity is therefore a well-defined property of the functional state space of any system.
Keywords: Environmental Sciences; Physical Sciences and Mathematics; Sustainability